Stone Garden Tourist Value: A Sociological Value Perspective - Syarifuddin, Didin (Media Wisata, 2022)
The high level of change in people's social life demands an increase in people's knowledge of their social behaviour, which has an impact on the growth of people's intelligence to adapt to changes in the social environment, including customers. Customers have become the target of attention for business organizations including Stone Garden, through increasing customer value. The study purpose is to explain the visitor value from a functional, social, emotional and spiritual perspective during their visit to Stone Garden, followed by the meaning of visitor values from a sociological perspective. The research method used is a quantitative descriptive method with a sample measure of 100 people, using the percentage formula followed by determining the range to determine the interval for assessing respondents' perceptions. The results showed that the functional, social, emotional and spiritual values were included in the excellent category. The high value of visitors becomes a reference in determining the sociological value. Stone Garden has become an important part of people's lives because it can provide benefits and be used as a reference for travelling for the community. Stone Garden has become a superior tourism model because it shows something different, namely rock-based natural tourism as the advantage vehicle. This advantage is a motivation for organizations that can foster confidence in the development of tourist destinations in the future as well as for the community so as to direct other people to visit Stone Garden.